An original recycling method for Li-ion batteries through large scale production of Metal Organic Frameworks - Cognet, Marine (2020)
A concept is proposed for the recycling of Li-ion batteries with an open-loop method that allows to reduce the volume of wastes and simultaneously to produce valuable materials in large amounts (Metal-Organic Frameworks, MOFs). After dissolution of Nickel, Manganese, Cobalt (NMC) batteries in acidic solution (HCl, HNO3 or H2SO4/H2O2), addition of organic moieties and a heat treatment, different MOFs are obtained. Solutions after precipitation are analyzed by inductively coupled plasma and materials are characterized by powder X-Ray diffraction, N2 adsorption, thermogravimetric analysis and Scanning electron microscope. With the use of Benzene-Tri-Carboxylic Acid as ligand, it has been possible to form selectively a MOF, based on Al metallic nodes, called MIL-96 in the literature, and known for its interesting properties in gas storage applications. The supernatant is then used again to precipitate other metals as MOFs after addition of a second batch of ligands. These two other MOFs are based on Cu (known as HKUST-1 in the literature) or Ni-Mn (with a new crystalline structure) depending of conditions. This method shows promising results at the lab scale (15 g of wastes can be converted in 10 g of MOFs), and opens interesting perspectives for the scaled-up production of MOFs.